Hubungan Pengetahuan Tentang Keputihan Dengan Upaya Pencegahan Keputihan Pada Remaja - Anil Masyayih , Warda; Siswati, Eny; Andariya Ningsih, Dewi (LPPM STIKES HUSADA JOMBANG, 2022)
Reproductive health in women cannot be separated from the health of their sex organs. Of course we need to realize that maintaining reproductive health is very important for us. One of the things we can do is maintain cleanliness or hygiene, especially in the area around the vagina.The research design used was a correlational analytic study with a cross sectional design approach. The sample of all adolescents in RT 01 / RW 02 Turirejo Lawang Village, Malang were 67 respondents using non-probability techniques: purposive sampling. The measuring instrument used was the observation sheet, the results were analyzed using the Spearman rho test with a significance level of 5% (α = 0.05).The results of this study indicate that having good knowledge of vaginal discharge and good leucorrhoea prevention efforts are 12 respondents (20.7%), respondents who have good knowledge of leucorrhoea and good leucorrhoea prevention efforts are 9 respondents (15.5%). Meanwhile, from the Spearman rho test, the sig value is obtained. (2-tailed) or ρ value 0.001 (because ρ value <0.05) then H0 is rejected and H1 is accepted.There is a significant relationship between knowledge of vaginal discharge and prevention efforts in adolescents, the better the knowledge of adolescents the better the prevention of leucorrhoea in adolescents.